Epidemiology of homicide: homicide method and demographic status of victim recorded at Sardjito General Hospital - Jessica, Theresia; Pidada, Surya; Widagdo, Hendro (BKM Public Health and Community Medicine, 2022)
Purpose: The study aims to find out associations between the demographic factors for a person to become a homicide victim in Indonesia and the possible method of homicide-related. We hypothesize that there is an association between the demographic status of the homicide victim and the homicide methods and even between the homicide method and incident time themselves. Methods: By using visum et repertum of the homicide victims that were recorded in dr. Sardjito General Hospital, Yogyakarta, Indonesia in 2005-2015. The baseline characteristics are above 15-year-old victims who lived in Bantul District, Sleman District, Yogyakarta City, Kulon Progo District, and Gunungkidul District with identified age, sex, and homicide method and had their incident time recorded in dr. Sardjito General Hospital. The victim’s age, sex, occupation, marital status, and socioeconomic were analyzed to determine if there is any association found to the homicide method that includes homicide method and incident time that the homicide occurred. The association within the homicide method was also analyzed using the same method. Results: Of the 105 homicide victims who had a Visum et Repertum made at the dr. Sardjito General Hospital, most of the homicide victims were male, 20-40 years old, worked for private, were married, had high socioeconomic status, were murdered by blunt force trauma with bleeding as a mechanism of death, during night time and in outside settings. The result shows that the homicide method is found to be significantly associated with sex, as socioeconomic status only affects females. Meanwhile, the incident time of the homicide is related to the age of the victim. The association between the two variables of the homicide method was only found if the victim is male, where poisoning is more likely to occur during daytime, and sharp object trauma is more likely to occur at night. Conclusion: Associations between homicide methods and some of the demographic statuses were found. Male victims with poisoning of homicide method are more likely to occur during the daytime, and sharp object trauma is more likely to occur at night.